Analisis Framing Pemberitaan Detikjateng.Com Dan Tribunjateng.Com Tentang Kasus Bullying Di Pelajar Jawa Tengah - Pinalis, Dallih; Triyono, Agus (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
The number of cases of bullying that occur in the school environment makes important attention in the world of education today, one of which is in Central Java. Thus making the mass media joined the rollicking to report the case. This research uses qualitative approach with Robert n framing analysis method. Etnman. The purpose of this study to determine the framing of news cases of bullying at the level of Central Java in the online media Detikjateng.com and Tribunjateng.com. Data were collected from news articles published in September 2023-February 2024. The results showed that the media Detikjateng.com and Tribunjateng.com has an important role in conveying information about bullying cases, focusing on several elements, namely physical, verbal and social bullying. In addition, the news also covers the handling of cases by the authorities and the psychological impact experienced by victims. This study emphasizes the need for more attention to the handling of cases of bullying as well as increased public awareness of this issue to create a safer educational environment for students.